2018
DOI: 10.3390/w10040414
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Measuring Microplastic Transport in Large or Medium Rivers

Abstract: Plastic waste as a persistent contaminant of our environment is a matter of increasing concern due to the largely unknown long-term effects on biota. Although freshwater systems are known to be the transport paths of plastic debris to the ocean, most research has been focused on marine environments. In recent years, freshwater studies have advanced rapidly, but they rarely address the spatial distribution of plastic debris in the water column. A methodology for measuring microplastic transport at various depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 35 publications
0
62
1
3
Order By: Relevance
“…A thorough examination of scientific literature on abundance, distribution patterns, and characteristics of microplastics in freshwater environments in Mediterranean tributary rivers has shown a substantial lack of information and the need to apply adequate and uniform measurement methods.have shown that MPs are present in different layers of the river-bed and of the water column (e.g. [20] or [21]). Classified according to the annual discharge, the ten largest Mediterranean tributary rivers are the Rhone, Po, Drin-Bojana, Nile, Neretva, Ebro, Tiber, Adige, Seyhan, and Ceyhan.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough examination of scientific literature on abundance, distribution patterns, and characteristics of microplastics in freshwater environments in Mediterranean tributary rivers has shown a substantial lack of information and the need to apply adequate and uniform measurement methods.have shown that MPs are present in different layers of the river-bed and of the water column (e.g. [20] or [21]). Classified according to the annual discharge, the ten largest Mediterranean tributary rivers are the Rhone, Po, Drin-Bojana, Nile, Neretva, Ebro, Tiber, Adige, Seyhan, and Ceyhan.…”
mentioning
confidence: 99%
“…have shown that MPs are present in different layers of the river-bed and of the water column (e.g. [20] or [21]).…”
mentioning
confidence: 99%
“…Costs are denoted as relative estimates ranging from "+" (lowest costs) to "+++" highest costs as actual costs may vary depending on supplier and chosen design specifics. References of method application [10,11], present study [2][3][4][5][6][7][8] [12] * = high density polymers (i.e., denser than water); ** = low density polymers (i.e., lighter than water).…”
Section: Experimental Work and Validation Resultsmentioning
confidence: 99%
“…If a lower sample volume is acceptable or if longer filter cartridges are used and operated separately, the system seems suitable for streamlined sampling of replicates, e.g., in short time intervals or at different positions at the same location. A recent study on MP monitoring underpinned the importance of replicated sampling throughout a river cross-section [5]. This is just one possible modification to adapt the system to specific sampling scenarios and we encourage others to contact us for requests or comments and to replicate or improve upon the suggested design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation